1970
DOI: 10.3329/jbcps.v28i1.4639
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Prelabour Rupture of the Membrane & Feto-Maternal out come: an Observational Study

Abstract: Objective: The aim of this study was to see the maternal and fetal outcome of preterm pre labor rupture membrane and to identify the risk factors for preterm pre labor rupture membrane. Methods and Material: This was a cross-sectional descriptive type study carried out in Dhaka Medical College Hospital, Dhaka, during April to September, 2005 (6months) in the Department of Obstetric and Gynecology. 50 pregnant women with preterm premature rupture of the membrane (gestational age 29-0 to 36-6 weeks) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 4 publications
8
28
3
Order By: Relevance
“…2 Triniti et al also reported the mean age of 29.8±7.2 years among patients with preterm premature rupture of membranes. 10 In this study PPROM was present in 50.1% of patients in the age group 21-30 years and the mean age was 26.3±6.9 years, which was comparable with the above studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 Triniti et al also reported the mean age of 29.8±7.2 years among patients with preterm premature rupture of membranes. 10 In this study PPROM was present in 50.1% of patients in the age group 21-30 years and the mean age was 26.3±6.9 years, which was comparable with the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study 61.1% were multigravida and 38.9% were primigravida which was comparable with study by Akter at al (multigravida 62% primigravida 38%). 2 Highest number of cases (56.3%) of PPROM occurred near to term (34-0 to 36-6weeks). The mean gestational age at the onset of membrane rupture was 34.1±2.4 weeks This was comparable with the study by Akter et al which showed 66% of cases of PPROM between 35-37 weeks of gestation and mean gestational age of 34.74±2.27weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations